2020
DOI: 10.1242/bio.047316
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of historical temperature regime and algal symbionts on the heat tolerance of coral juveniles

Abstract: The rate of coral reef degradation from climate change is accelerating and, as a consequence, a number of interventions to increase coral resilience and accelerate recovery are under consideration. Acropora spathulata coral colonies that survived mass bleaching in 2016 and 2017 were sourced from a bleaching-impacted and warmer northern reef on the Great Barrier Reef (GBR). These individuals were reproductively crossed with colonies collected from a recently bleached but historically cooler central GBR reef to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 75 publications
(102 reference statements)
6
60
0
Order By: Relevance
“…We observed a significant negative correlation between the proportion of D. trenchii and polyp size after 5 months, consistent with previous studies reporting reduced growth in juvenile and adult corals hosting D. trenchii (Little et al 2004; Cantin et al, 2009; Jones & Berkelmans 2010; Pettay et al 2015; but see Yuyama & Higuchi 2014; Quigley et al 2020). For instance, Little et al (2004) found that acroporid recruits infected with Cladocopium grew 2-3 times faster than those hosting Durusdinium .…”
Section: Discussionsupporting
confidence: 91%
“…We observed a significant negative correlation between the proportion of D. trenchii and polyp size after 5 months, consistent with previous studies reporting reduced growth in juvenile and adult corals hosting D. trenchii (Little et al 2004; Cantin et al, 2009; Jones & Berkelmans 2010; Pettay et al 2015; but see Yuyama & Higuchi 2014; Quigley et al 2020). For instance, Little et al (2004) found that acroporid recruits infected with Cladocopium grew 2-3 times faster than those hosting Durusdinium .…”
Section: Discussionsupporting
confidence: 91%
“…Studies using juveniles produced from the hybridisation of gametes sourced from different coral populations have shown either negligible (Quigley et al, 2016) or strong effects of local adaptation (i.e., no survival benefits) (van Oppen et al, 2014), in which the difference in effect size may be driven by the outplant environment (northern × central hybrids to central site or central × southern hybrids to southern site). In the laboratory, several-fold benefits in survival and growth were recorded in hybrid juveniles with at least one warm-adapted dam and in symbiosis with Durusdinium symbionts (Quigley et al, 2020a). Taken together, results in corals from reciprocal translocations and population hybridisation show promise in understanding their use as intervention strategies to enhance the adaptive responses of corals to increasingly warm oceans.…”
Section: Introductionmentioning
confidence: 87%
“…Although encouraging, due to the costs and risks associated with human interventions, it is important that future models are based on empirical biological and environmental data explicit for specific populations targeted for intervention. This requires that further experimental studies, like those currently underway 20,[24][25][26][27] continue to fill in the knowledge gaps on the genomic underpinnings of traits related to climate change adaptation in corals.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Therefore, a detailed understanding of the genetic architecture of fitness related traits, including epistasis and linkage maps; as well as the trade-offs among traits is critical for improved evolutionary modelling efforts in the future. Additionally, and especially important on coral reefs, the contribution of microbial partners to the phenotypes of their hosts is increasingly recognised 37 , and the interplay between the evolution of the host organism and its microbial associates cannot be neglected in coral adaptation models 23,25,38,39 .…”
Section: Implications For Interventionsmentioning
confidence: 99%